Classification of upper limb spasticity patterns in patients with multiple sclerosis: a pilot observational study - Mirko Filippetti; Linde Lugoboni; Rita Di Censo; Luca Degli Esposti; Salvatore Facciorusso; Valentina Varalta; Andrea Santamato; Massimiliano Calabrese; Nicola Smania; Alessandro Picelli (Medical Journals Sweden, 2024)
Objective: The aim of this study was to provide a classification of the upper limb patterns in patients with upper limb spasticity due to multiple sclerosis. Design: Pilot observational study. Patients: Twenty-five adult patients with multiple sclerosis suffering from upper limb spasticity who underwent one segmental (i.e., proximal and distal upper limb) botulinum toxin treatment cycle were recruited. Methods: Patients remained in a sitting position during the evaluation. Upper limb spasticity postures (i.e., postural attitude of a single joint/anatomical region) were evaluated and recorded for the shoulder (adducted/internally rotated), elbow (flexed/extended), forearm (pronated/supinated/neutral), wrist (flexed/extended/neutral) and hand (fingers flexed/thumb in palm). Results: On the basis of the clinical observations, 6 patterns (i.e., sets of limb postures) of upper limb spasticity have been described according to the postures of the shoulder, elbow, forearm, and wrist. Conclusion: The patterns of upper limb spasticity in patients with multiple sclerosis described by this pilot study do not completely overlap with those observed in patients with post-stroke spasticity. This further supports the need to consider the features of spasticity related to its aetiology in order to manage patients appropriately.